The Effect of Heart Rate Variability Biofeedback Training on Optimizing Blood Pressure after Exercising in Cold Environment in 14-15-Year-Old Adolescents - Liliya V. Poskotinova (International Journal of Biomedicine)
Background: The heart rate variability biofeedback (HRV-BF) method is designed to activate both vagal nerve activity and baroreflex function. The present study aimed to determine the relation between the expression of the spectral power of the dominant peak of the HRV low-frequency (LF) band, its time period, and the degree of blood pressure decrease in 14-15-year-old adolescents who performed short-term HRV-BF training after physical exercise in a cold environment. Methods and Results: Thirty healthy 14–15-year-old males were examined. The study included the baseline stage, physical activity in the cold, post-exercise stage, recovery stage—HRV-BF training (the HRV-BF group, n=20), or resting stage (the control group, n=10). In the control group, systolic blood pressure (SBP) did not change significantly at any examination stage. In the HRV-BF group, the SBP level was significantly lower in the recovery stage than at baseline (110.0 [108.0; 117.0] mmHg and 115.0 [110.0; 128.0] mmHg, respectively, P=0.008), which occurred against the background of an increase in the LF band (2.16 [0.94; 4.62] ×1000, ms2 versus 0.75 [0.47; 0.92]×1000, ms2 in the control group, P<0.01) and spectral power of the maximum LF peak (LFmx) (97.9 [32.5; 247.6] ms2/Hz versus 33.5 [23.6; 46.1] ms2/Hz in the control group, P<0.05). Conclusions: Short-term HRV-BF training to enhance the overall HRV after exercise in the cold provides a more pronounced reduction in post-load elevated SBP than in the group without this training, against the background of an increase in the HRV LF band and spectral power of the maximum peak of the LF band.